2017
DOI: 10.1055/s-0037-1615748
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Male and Female Prolactinoma Patients Requiring Surgical Intervention

Abstract: Prolactinomas are the most common functional pituitary adenoma. Symptoms of a prolactinoma stem from hormonal causes (menstrual irregularities, galactorrhea, and reduced libido) or from tumor mass effect (visual changes and headache). Gender differences have been noted in prolactinomas, with males presenting with larger tumors and sequelae of mass effect, while females present commonly with hormonal symptoms. The purpose of this study is to evaluate differences in patient and disease characteristics, and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…Overall, the cluster of elements used for evaluating the potential aggressive behavior starts with high prolactin levels at first admission and large diameter upon computed tomography or magnetic resonance imaging; yet these themselves do not necessarily indicate an APRL (27,28). If the patient is a male or there is an early age at diagnosis or a genetic predisposition is identified, the prognosis may be poor (27,29). Furthermore, the development of DA (mostly cabergoline) resistance represents another useful clue (27,30).…”
Section: Presentationmentioning
confidence: 99%
“…Overall, the cluster of elements used for evaluating the potential aggressive behavior starts with high prolactin levels at first admission and large diameter upon computed tomography or magnetic resonance imaging; yet these themselves do not necessarily indicate an APRL (27,28). If the patient is a male or there is an early age at diagnosis or a genetic predisposition is identified, the prognosis may be poor (27,29). Furthermore, the development of DA (mostly cabergoline) resistance represents another useful clue (27,30).…”
Section: Presentationmentioning
confidence: 99%
“…Prolactinomas are more often missed in men than women due to subtle non-specific symptoms (see Clinical features ) in the former, whereas in women a relatively mild hyperprolactinaemia usually causes menstrual disturbance (oligo-amenorrhoea/ amenorrhoea) 1011. Men often fail to seek medical advice due to embarrassment or denial about their lowered libido or erectile dysfunction or attributing them to other factors, leading to larger prolactinomas at diagnosis 1011…”
Section: Why Is It Missed?mentioning
confidence: 99%
“…Men often fail to seek medical advice due to embarrassment or denial about their lowered libido or erectile dysfunction or attributing them to other factors, leading to larger prolactinomas at diagnosis 1011…”
Section: Why Is It Missed?mentioning
confidence: 99%
“…Finally, in prolactinomas with mass effect surgery or radiosurgery may be indicated, however, there is a greater probability of hypopituitarism and recurrence (12). Other indications for surgical treatment include intolerance to the side effects of medications, the desire to become pregnant, or those related to the patient's preference (13).…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al (13) described that men undergoing resection surgery were less likely to normalize serum prolactin levels, since the tumor is more aggressive and is able to spread to the suprasellar region or the cavernous sinus. In the review by Penn et al (14) they showed that even though surgical treatment of prolactinoma is a safe procedure, with efficacy in hormonal and symptom control, it is less likely that it will not remit with surgery alone in men.…”
Section: Introductionmentioning
confidence: 99%